Pengaruh Corporate Culture, Motivasi Karyawan, Dan Inovasi Organisasi Terhadap Praktik Kepemimpinan Transformasional di PT KAI Daop 6 Yogyakarta - Surya Darmawan; Adi Prasetyo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of corporate culture, employee motivation, and organizational innovation on transformational leadership practices at PT KAI DAOP 6 Yogyakarta. This study uses a quantitative approach with a survey method. The sample was determined using a purposive sampling technique, and the questionnaire was compiled using a five-point Likert scale. A total of 95 respondents who were permanent employees of PT KAI DAOP 6 Yogyakarta with a minimum work period of one year were involved in this study. The research instrument was a closed questionnaire, and the analysis technique used was multiple linear regression. The results of the analysis showed that, both partially and simultaneously, corporate culture, employee motivation, and organizational innovation had a positive and significant effect on transformational leadership practices. This study is expected to provide practical implications for the development of leadership strategies and human resource management in public transportation organizations.